Location-based Adaptive Beamforming and Beam Steering for Mobile Communication in Multipath Environments (London Journal of Engineering Research, 2024)
This paper investigates location-based adaptive beamforming techniques, including Maximum Ratio Transmission (MRT) and Zero Forcing (ZF), in complex wireless environments. The study leverages a digital twin simulation of the University of Glasgow campus to evaluate the proposed schemes under realistic conditions, such as user mobility and multipath propagation. The results demonstrate significant performance improvements with the location-based beam steering approaches. In the open space scenario, the location-based schemes achieved up to 40% higher Signal-to-Interference-plus-Noise Ratio (SINR) and 30% higher received power, along with reduced interference. The gains were even more pronounced in the digital twin environment, with up to 50% improvement in SINR and 40% increase in received power. Furthermore, the study evaluates the energy efficiency of the location-based adaptive beamforming techniques, showing up to 20% reduction in energy consumption compared to conventional fixed-beam approaches.
Keywords: Adaptive Beamforming; Beam Steering; Location Estimation; Smart Antenna Systems